2017
DOI: 10.1186/s12872-017-0520-7
|View full text |Cite
|
Sign up to set email alerts
|

miR-21 enhances cardiac fibrotic remodeling and fibroblast proliferation via CADM1/STAT3 pathway

Abstract: BackgroundCardiac fibrosis play a key role in the atrial fibrillation pathogenesis but the underlying potential molecular mechanism is still understood. However, potential mechanisms for miR-21 upregulation and its role in cardiac fibrosis remain unclear. The controls cell proliferation and processes fundamental to disease progression.MethodsIn this study, immunohistochemistry, real-time RT-PCR, cell transfection, cell cycle, cell proliferation and Western blot were used, respectively.ResultsHere we have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 18 publications
2
52
0
Order By: Relevance
“…miR-21 upregulation in plasma has been proposed as an indicator for cardiac fibrotic remodeling in young diabetic patients. 35 miR-21 was also reported to prevent type 1 diabetes in mice; it is involved in a regulatory pathway of beta-cell death, where it decreases the level of PDCD4 protein that induces death of pancreatic beta cells, thereby and did not differ significantly between T1DM, controls and GCK-MODY patients from our profiling cohort.…”
Section: Takahashi Et Al Reported Higher Let-7g Expression In Pbmcs mentioning
confidence: 64%
See 1 more Smart Citation
“…miR-21 upregulation in plasma has been proposed as an indicator for cardiac fibrotic remodeling in young diabetic patients. 35 miR-21 was also reported to prevent type 1 diabetes in mice; it is involved in a regulatory pathway of beta-cell death, where it decreases the level of PDCD4 protein that induces death of pancreatic beta cells, thereby and did not differ significantly between T1DM, controls and GCK-MODY patients from our profiling cohort.…”
Section: Takahashi Et Al Reported Higher Let-7g Expression In Pbmcs mentioning
confidence: 64%
“…Also, significantly higher levels of miR‐21 were previously reported in PBMCs and in plasma of T1DM patients. miR‐21 upregulation in plasma has been proposed as an indicator for cardiac fibrotic remodeling in young diabetic patients . miR‐21 was also reported to prevent type 1 diabetes in mice; it is involved in a regulatory pathway of beta‐cell death, where it decreases the level of PDCD4 protein that induces death of pancreatic beta cells, thereby potentially preventing T1DM .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, recent studies reveal additional mechanisms underlying the role of miR‐21 in cardiac fibrosis. Cao et al reported that tumour suppressor cell adhesion molecule 1 (CADM1) is the potential target of miR‐21 and miR‐21 enhances cardiac fibrotic remodelling and fibroblast proliferation via targeting CADM1. Yuan et al found that miR‐21 promoted cardiac fibrosis after MI via targeting Smad7.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miR-21 has been ascribed a crucial role in the regulation of cellular activity during physiological and pathological processes [31]. miR‑21 is widely expressed and has been found to be increased in organs and tissues which have suffered fibrogenesis or remodeling, including the heart [32], kidney [33], lung [34], asthmatic airways [35, 36], liver [37, 38], skin [39-41], and tumor tissue [42, 43]. Studies revealed that enhanced miR-21 expression is involved in the progression of lung fibrosis, and TGF-β1 plays an important role in mediating increased miR-21 expression [34, 44].…”
Section: Introductionmentioning
confidence: 99%